Too Complex or Too Ambitious? Exploring Hurdles in the Enforcement of EU Free Trade Agreements - Biffi, Leopoldo (eCahiers de l'Institut, 2021)
This ePaper looks at the recent politics of EU trade, and specifically at the political hurdles characterising the enforcement of free trade agreements (FTAs) negotiated by the European Commission. It argues that civil society advocacy groups have played a key, yet undertheorised, role in accounting for the recent politicisation of a number of EU FTAs, which has often translated into obstacles to ratification. The TTIP, the CETA, and the EU-Mercosur FTA constitute relevant examples. The analysis privileges a Commission standpoint, conceiving ratification hurdles as public-management issues tackled by Brussels in view of rescuing its trade-policy mandate from domestic vetoes. We argue that the Commission is particularly compelled to implement FTA reviews and safeguards when advocacy concerns are endorsed by official-level policy actors like the European Parliament, enjoying ultimate veto powers. In a final step, the research also enquires into the narrower reality of mixed FTAs, focusing on the case study of the CETA. In this regard, it suggests that prolonged national-level ratification poses no extraordinary obstacle to the Commission, as treaty enforcement is aided by lock-in dynamics involving both official-level and civil-society veto players - even in the absence of full de jure ratification. We conclude that, while the above ratification obstacles have been addressed by the Commission on an ad hoc basis, as contingent policy issues, their prolonged occurrence suggests that they will need to be tackled more systematically in the future. This will require operating at the level of treaty-design, by addressing pressing concerns like trade and sustainable development more thoroughly and bindingly ahead of concluding negotiations - in view of preventing otherwise inescapable enforcement hurdles.